Analisis Konten Video Animasi YouTube dalam Mendukung Indikator Keterampilan Berpikir Kritis pada Materi Perubahan Wujud Benda - Esia Esia; Nia Astuti; Fatma Zuhra (Universitas Garut, 2026)
This study aims to analyze the integration of critical thinking indicators in a technology-based animated video entitled Changes in the Form of Things on the topic of changes in the states of matter. The research employed a qualitative approach using content analysis as the primary method. The analytical framework was based on Robert H. Ennis’s critical thinking indicators, which include problem clarification, assessment of evidence, inference, and reasoning. The data consisted of narrative structure, visual representations, empirical examples, and patterns of argumentation presented in the video. Data analysis was conducted through data reduction, indicator categorization, and cognitive interpretation of how each indicator was represented within the content structure. The findings reveal that all four critical thinking indicators are present in the video; however, they appear in basic and implicit forms. The indicators of problem clarification and inference are the most dominant, reflected in the presentation of definitions, conceptual classifications, and explicit cause–effect explanations delivered by the narrator. Meanwhile, the indicators of assessment of evidence and reasoning appear in simpler forms, primarily limited to illustrative examples and linear causal relationships without exploration of alternative variables or critical evaluation. Structurally, critical thinking is more often presented as an outcome of information delivery than as a reflective cognitive process that actively engages learners. These findings indicate that the video is effective in supporting basic conceptual understanding but has not yet optimally stimulated higher-order thinking skills. Therefore, strengthening instructional design through problem-based or inquiry-based approaches is necessary so that technology-based learning media function not only as tools for knowledge transmission but also as facilitators for the comprehensive development of critical thinking skills.Keywords: Animated, critical thinking, change, Ennis, thinking